Lipid metabolism in tumor immunology and immunotherapy - Duong, Lisa K.; Corbali, Halil Ibrahim; Riad, Thomas S.; Ganjoo, Shonik; Nanez, Selene; Voss, Tiffany; Barsoumian, Hampartsoum B.; Welsh, James; Cortez, Maria Angelica (Frontiers in Oncology, 2023)
Lipids are a diverse class of biomolecules that have been implicated in cancer pathophysiology and in an array of immune responses, making them potential targets for improving immune responsiveness. Lipid and lipid oxidation also can affect tumor progression and response to treatment. Although their importance in cellular functions and their potential as cancer biomarkers have been explored, lipids have yet to be extensively investigated as a possible form of cancer therapy. This review explores the role of lipids in cancer pathophysiology and describes how further understanding of these macromolecules could prompt novel treatments for cancer.